Review of Evolocumab for the Reduction of LDL Cholesterol and Secondary Prevention of Atherosclerotic Cardiovascular Disease - Lawrence A. Leiter; Robert A. Hegele; Vivien Brown; Jean Bergeron; Erin S. Mackinnon; G. B. John Mancini (Reviews in Cardiovascular Medicine, 2024)
Elevated low-density lipoprotein cholesterol (LDL-C) is a major causal factor for atherosclerotic cardiovascular disease (ASCVD), the leading cause of mortality worldwide. Statins are the recommended first-line lipid-lowering therapy (LLT) for patients with primary hypercholesterolemia and established ASCVD, with LLT intensification recommended in the substantial proportion of patients who do not achieve levels below guideline-recommended LDL-C thresholds with statin treatment alone. The proprotein convertase subtilisin/kexin type 9 inhibitor monoclonal antibody evolocumab has demonstrated significant LDL-C reductions of >60% in the clinical trial and open-label extension settings, with LDL-C reductions observed early post-evolocumab initiation and maintained long term, during up to 8.4 years of follow-up. Evolocumab therapy, when added to a statin, also conferred a significant reduction in major cardiovascular (CV) events, including a 20% reduction in the composite of CV death, myocardial infarction (MI), or stroke. The absolute benefits were enhanced among various patient types at high and very high risk for secondary ASCVD (e.g., with recent MI, multiple events or peripheral artery disease). Importantly, evolocumab treatment resulted in incremental CV risk reductions during the extended follow-up, including a 23% reduction in CV mortality and no apparent LDL-C level below which there is no further CV risk reduction. Hence, the evolocumab clinical data support the need for early and significant LDL-C lowering, especially in vulnerable ASCVD patients, in order to derive the greatest benefit in the long term. Importantly, evolocumab had no impact on any treatment emergent adverse events apart from a small increase in local injection site reactions. A growing body of real-world evidence (RWE) for evolocumab in heterogeneous populations is consistent with the trial data, including robust LDL-C reductions below guideline-recommended thresholds, a favourable safety profile even at the lowest levels of LDL-C achieved, and a high treatment persistence rate of >90%. Altogether, this review highlights findings from 50 clinical trials and RWE studies in >51,000 patients treated with evolocumab, to demonstrate the potential of evolocumab to address the healthcare gap in LDL-C reduction and secondary prevention of ASCVD in a variety of high- and very high-risk patients.